Endovascular thrombectomy with versus without intravenous thrombolysis in patients with acute basilar artery occlusion: a systematic review and meta-analysis - Cai, Lingyu; Wang, Liaoyuan; Campbell, Bruce C. V.; Wu, Yuelu; Abdalkader, Mohamad; Alemseged, Fana; Kaesmacher, Johannes; Puetz, Volker; Nagel, Simon; Strbian, Daniel; Knapen, Robrecht R. M. M.; Li, Chuanhui; et al. (Journal of neurology, 2024)
The benefit and safety of intravenous thrombolysis before endovascular thrombectomy in patients with acute ischemic stroke caused by basilar artery occlusion (BAO) remains unclear. This article aims to investigate the clinical outcomes and safety of endovascular thrombectomy with versus without intravenous thrombolysis in acute BAO stroke patients.
Gesehen am 08.10.2024